Association between the Lynch syndrome gene MSH2 and breast cancer susceptibility in a Canadian familial cancer registry. Issue 11 (4th August 2017) - Goldberg, Mira; Bell, Kathleen; Aronson, Melyssa; Semotiuk, Kara; Pond, Greg; Gallinger, Steven; Zbuk, Kevin
Abstract : Background: Previous studies assessing breast cancer risk in families with Lynch syndrome (LS) have yielded conflicting results. Furthermore, conclusions are limited by small sample size and few breast cancer outcomes. This study assesses breast cancer risk in a large prospectively followed LS cohort. Methods: Pedigrees of 325 unrelated families with LS within the Familial Gastrointestinal Cancer Registry in Canada were examined for breast cancer diagnoses. Standardised incidence ratios (SIR) and lifetime cumulative incidence calculations were used to compare the incidence of breast cancer in mutation carriers with the general population. Results: Forty-one mutation carriers diagnosed with breast cancer belonging to 34 unrelated families were identified. Mean age at diagnosis was 54 years. The mutation distribution among the LS patients with breast cancer was statistically different from those without breast cancer (p=0.015), reflecting the predominance of MSH2 mutations among affected patients (74%). Eighty-eight per cent of LS families with breast cancer met Amsterdam criteria, compared with 49% of LS families without breast cancer (p=0.03). Lifetime cumulative incidence of breast cancer in female MSH2 mutation carriers in our cohort was 22% (p<0.001). The SIR for breast cancer of female MSH2 mutation carriers in our cohort was 3.11 (95% CI 1.95 to 4.71). Conclusions: An increased risk of breast cancer in MSH2 mutation carriers was demonstrated in a Canadian familial cancer registry. Women with breast cancer often had a personal and family history of multiple LS-related malignancies. These results suggest a potential role for intensified breast cancer surveillance among women with LS.